2001
DOI: 10.1046/j.1365-2125.2001.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective halofantrine disposition and effect:concentration‐related QTc prolongation

Abstract: Aims 1) To characterize the variability of multiple-dose halofantrine pharmacokinetics over time in healthy adults, 2) to correlate the pharmacodynamic measure electrocardiographic (ECG) QT interval with (+)-and (x)-halofantrine plasma concentration and 3) to evaluate the safety and tolerance of halofantrine hydrochloride given over time to healthy adults. Methods Twenty-one healthy subjects were enrolled and 13 completed the study (180 days). Subjects received either 500 mg of racemic halofantrine once daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 29 publications
6
27
0
Order By: Relevance
“…These findings likely reflect a gradual change to the proportion of the (+) enantiomer present in systemic blood. Previous data have shown that systemic levels of the (+)-Hf enantiomer in both human and rat are approximately 1.5 times higher than its antipode [1][2][3][4][5][6][7], and preliminary plasma assays performed in our laboratory have indicated that the same trend is followed in the dog (data not shown). At later time periods, when intestinal lymphatic transport has slowed, an increasing proportion of the Hf in thoracic lymph is present as a result of equilibration of Hf across lymphatic and blood capillaries.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…These findings likely reflect a gradual change to the proportion of the (+) enantiomer present in systemic blood. Previous data have shown that systemic levels of the (+)-Hf enantiomer in both human and rat are approximately 1.5 times higher than its antipode [1][2][3][4][5][6][7], and preliminary plasma assays performed in our laboratory have indicated that the same trend is followed in the dog (data not shown). At later time periods, when intestinal lymphatic transport has slowed, an increasing proportion of the Hf in thoracic lymph is present as a result of equilibration of Hf across lymphatic and blood capillaries.…”
Section: Resultssupporting
confidence: 65%
“…relative enrichment of the (+)-enantiomer (data not shown) [1][2][3][4][5][6][7]. transport of the drug-lipoprotein complex via the intestinal lymphatic to the thoracic lymph.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, the pharmacokinetic results of DHF enantiomers after administration of parent drug in rat are paralleled by those in humans, in which plasma concentrations of (+)-DHF exceed those of antipode [5,15,16].…”
Section: Discussionmentioning
confidence: 70%
“…ECGs were recorded at 4,8,12, and 48 h following drug administration. Vital signs were measured throughout the study.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…The declining sensitivity of P. falciparum to halofantrine may necessitate an increase in dosage, but the cardiotoxic effects of the drug are a major concern, especially as they are plasma concentration-dependent [4]. Therefore it is important that strategies are devised to prevent the further spread of halofantrine resistance and to delay its onset in areas where the drug is still effective.…”
Section: Introductionmentioning
confidence: 99%